Civic education as social process: A case study of students’ protests in Córdoba, Argentina, 2010 - Miguez, Daniel Pedro (2018)
This article’s aim is to provide, through a case study, new insights into current research on the civic education policies that encompassed the transition from authoritarian to democratic political regimes that took place as of the final years of the 20th century in Africa, Eastern Europe and Latin America. Many of these studies parted from the assumption that citizenship could be promoted by imparting a universal set of rights and attitudes, which would not interact with pre-existent and varied conceptions of citizenship. By studying the midlevel students’ protests that took place in the city of Córdoba in Argentina in 2010, we show that even in societies that have undergone long dictatorial periods, there are pre-existent civic traditions that influence the implementation and effects of these policies. This leads to new recommendations on the importance of considering these traditions when designing and assessing civic education policies.